Recent Progress in Ruthenium Oxide‐Based Composites for Supercapacitor Applications - Majumdar, Dipanwita; Maiyalagan, Thandavarayan; Jiang, Zhongqing (ChemElectroChem, 2019)
Electrochemical energy storage has emerged as one of the principal topics of present‐day research to deal with the high energy demands of modern society. Accordingly, besides fuel cells and battery technologies, interesting and challenging results have been observed in the recent past, during the materialization of “supercapacitors” or “ultracapacitors”, which have provoked a sharp increase in research inclination to revisit this aspect of renewable and sustainable energy storage. Supercapacitor performances are largely dependent on electrode materials, the nature of the electrolyte used, and the range of voltage windows employed. Carbon‐based electrode materials have tunable properties such as electrical conductivity, extensive surface area, and faster electron transfer kinetics with low fabrication costs. But their specific capacitances are found to be too low for commercialization. Ruthenium dioxide (RuO2), owing to its high theoretical specific capacitance value (1400–2000 F g−1), has been extensively recognized as a favorable material for supercapacitor devices, but high production cost and agglomeration effects stand as high barriers preventing marketable usage. Consequently, RuO2‐based nanocomposites have been widely studied to optimize the material cost, with simultaneous improvement in the electrochemical performances. This Review describes comprehensively the recent progress in terms of the fabrication and design, electrochemical performance, and achievements of RuO2 and its nanocomposites as electrode materials for supercapacitors, which will be beneficial for further research designing high‐performance supercapacitor devices. Where did you come from, where do you go?RuO2‐based nanocomposites have been widely studied for the improvement of the electrochemical performances of next‐generation supercapacitors and supercapatteries. The present Review article aims to describe comprehensively the recent progresses in terms of the fabrication and design, electrochemical performance, and achievements of RuO2 and its nanocomposites as electrode materials for supercapacitors.